The last sunrise - Ryan, Robert 1951- (Headline Review, 2006)
1948: INDO-CHINA. Lee Crane is an American pilot flying demobbed air transports - C47 Dakotas - across South-East Asia for the highest bidder. He'll fly anywhere, if the price is right. But his experiences during the war are haunting him, and when he meets a woman from the past, it is, literally, a slap in the face. 1941: BURMA. Crane is a young and innocent airman, flying P-40 Tomahawk fighter planes for the notorious Flying Tigers, the American Volunteers who are helping the Allies push back the Japanese. But when he falls for the charms of a beautiful Anglo-Indian girl she has a devastating effect on him. As the Japanese create chaos in Indo-China and all around him people are looting and lining their pockets, Crane desperately needs to return to find his Indian lover, no matter what the cost.